2022
DOI: 10.1186/s12889-022-14277-4
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative exploration of perceived barriers of exclusive breastfeeding among pregnant teenagers in the Greater Accra Region of Ghana

Abstract: Background The World Health Organization endorses exclusive breastfeeding for the first six months of every child’s life since exclusive breastfeeding has the potential of saving thousands of infants’ lives. The global exclusive breastfeeding rate among mothers is sub-optimal. This predisposes infants born to teenage mothers to all types of ailments. Therefore, this study explored the factors that inhibit the practice of exclusive breastfeeding as perceived by pregnant teenagers in the Greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“… 13 Factors such as negative feelings, perceived self-inefficacy, disapproval of exclusive breast feeding by relatives, social myths among others were mentioned to contribute to poor practice of exclusive breast feeding among adolescent mothers. 14 Also, a qualitative study by Tampah-Naah et al in a rural community in Ghana revealed that breastfeeding mothers under 19 years were easily influenced negatively regarding breast feeding by their society. 15 …”
Section: Introductionmentioning
confidence: 99%
“… 13 Factors such as negative feelings, perceived self-inefficacy, disapproval of exclusive breast feeding by relatives, social myths among others were mentioned to contribute to poor practice of exclusive breast feeding among adolescent mothers. 14 Also, a qualitative study by Tampah-Naah et al in a rural community in Ghana revealed that breastfeeding mothers under 19 years were easily influenced negatively regarding breast feeding by their society. 15 …”
Section: Introductionmentioning
confidence: 99%